"Stock Market Reaction on Budget 20 I 0" (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Finance Minister Pranab Mukherjee  on Friday 26 February, 2010 came  out with a Union Budget 2010 that  could be described as a fine balancing  act. The Union Budget 2010 managed  to spring up quite a f ew surprises.  With the Indian Stock Markets  anxiously waiting for the budget, it  was a stock market friendly budget to  say the least. While a lower fiscal  deficit in the financial year ahead,  resulting in a lower government  borrowing, soothed the stock markets'  nerves, an overhauled personal tax  structure provided relief to individual  taxpayers. Not surprisingly, stock  markets gave a rousing welcome to  the Budget and rose immediately as  the FM presented his speech.
Keywords: Finance Minister; Union Budget; Stock Markets; personal tax